2010
DOI: 10.1017/s0959270910000122
|View full text |Cite
|
Sign up to set email alerts
|

Avian collisions with power lines: a global review of causes and mitigation with a South African perspective

Abstract: SummaryMany large terrestrial and wetland birds and some smaller, fast-flying species are prone to colliding with overhead wires associated with power infrastructure. A high proportion of these are threatened species and for some, collision with power lines and other man-made structures is a significant and damaging source of anthropogenic mortality. We review the existing literature on the nature, scale and impact of this problem worldwide, with particular emphasis on the South African situation, and focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
118
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 17 publications
8
118
0
3
Order By: Relevance
“…The issue of collision and electrocution probably needs more investigation, as some could argue that the size, length of wing and position of the carcasses do not always indicate the actual cause of death. JENKINS et al (2010) suggested that the vulnerability of a species to collision with power lines is defined by a combination of the exposure to collision risk and the susceptibility of the species to collision. Studies from other areas suggested that large birds are more susceptible to collision along with the vegetation cover, density of predators, the size of the bird and the terrain of the area (CURRY & KERLINGER 2002, DIETER et al 2000, RUGGE et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of collision and electrocution probably needs more investigation, as some could argue that the size, length of wing and position of the carcasses do not always indicate the actual cause of death. JENKINS et al (2010) suggested that the vulnerability of a species to collision with power lines is defined by a combination of the exposure to collision risk and the susceptibility of the species to collision. Studies from other areas suggested that large birds are more susceptible to collision along with the vegetation cover, density of predators, the size of the bird and the terrain of the area (CURRY & KERLINGER 2002, DIETER et al 2000, RUGGE et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Many species of birds are especially vulnerable to collisions with high voltage transmission lines because of the height of these structures with respect to flight altitude, and because of their low visibility, whereas many species are potentially less vulnerable to collisions with distribution lines-the network of lower voltage lines that carry electricity to customers from load centers (Morkill and Anderson 1991, Jenkins et al 2010, APLIC 2012. Specifically, the shield wires, typically the highest wire found on transmission lines, are usually smaller in diameter than conductor wires, which renders them less visible (Brown et al 1987, Faanes 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Jenkins et al (2010), o número de linhas de energia elétrica no mundo aumenta a uma taxa de 5% a cada ano. Essas linhas acabam por formar redes extensas que atravessam diferentes habitat, entre eles alguns de extrema relevância para a avifauna, como corredores ou rotas de voo regulares entre áreas de alimentação e dormitório, caracterizados por grande tráfego de aves (Scott et al, 1972;Crivelli et al, 1988).…”
unclassified
“…Embora a preocupação com interações entre aves e LTs date desde o século passado (Michener, 1928), o número de publicações tem aumentado principalmente nas últimas quatro décadas, abrangendo diferentes países na Europa (Scott et al, 1972;Alonso et al,1994;Janss & Ferrer, 1998;Janss, 2000;Bevanger & Broseth, 2001;Rubolini et al, 2005;Barrientos et al, 2012;Martínez et al, 2016), África (Shaw et al, 2010;Jenkins et al, 2010;Krüger et al, 2015), América do Norte (Brown & Drewien, 1995;Savereno et al, 1996;Rioux et al, 2013;Sporer et al, 2013) e América do Sul (De La Zerda & Rosseli, 2003;Raposo, 2013). No Brasil, trabalhos sobre colisão de aves com estruturas de LTs ainda são escassos e limitados a estudos de licenciamento de impacto ambiental (Raposo, 2013).…”
unclassified
See 1 more Smart Citation